Pumpkin seed oil protects SH-SY5Y cells against amyloid-beta 42-induced oxidative stress and neuronal cell death - Areebambud, Chonticha; Sareedenchai, Vipaporn; Jariyapongskul, Amporn; Tadtong, Sarin (Science, Engineering and Health Studies, 2023)
Amyloid-beta (Aβ) peptide causes neuronal oxidative stress and eventual neuronal cell death. Pumpkin seed oil (PSO) contains fatty acids with antioxidant properties. The present study aimed to investigate the effect of PSO on amyloid-beta 42 (Aβ42) peptide-induced oxidative stress and neuronal cell death in human neuroblastoma SH-SY5Y cells. SH-SY5Y cells were pretreated with 0.001 and 10 μg/mL of PSO, following exposure to 1.25 μM of Aβ42 peptide. Aβ42-induced neuronal toxicity was characterized by decreased cell viability and Bcl-2 level and increased intracellular reactive oxygen species (ROS), Bax, and procaspase-3 levels. PSO pretreatment attenuated the Aβ42-induced loss of cell viability and neuronal cell death. The mechanisms by which PSO protects neuronal cells from oxidative stress include reducing levels of intracellular ROS, Bax, and procaspase-3, and increasing Bcl-2 levels. Based on our findings, the beneficial properties of PSO could be explored in future studies on co-treatment with modern medicine to prevent or slow cognitive impairment progression in Alzheimer’s disease.